Feminine Consciousness in Urdu Literature: A Critical Study of Contemporary Short Stories - بہار احمد (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This paper explores the concept of feminine consciousness in contemporary Urdu short stories, examining how female writers and some male writers represent the inner world, struggles, and agency of women. The study analyzes selected short stories by writers such as Ismat Chughtai, Khalida Hussain, and Asad Muhammad Khan to understand the evolution of feminine perspectives and their socio-cultural implications. اردو:یہ مقالہ اردو کے عصری افسانوں میں نسوانی شعور کے تصور کا جائزہ لیتا ہے، جس میں خواتین مصنفین اور بعض مرد افسانہ نگاروں کی جانب سے عورت کے داخلی احساسات، جدوجہد اور خود اختیاری کی عکاسی کو موضوع بنایا گیا ہے۔ اس مطالعے میں عصمت چغتائی، خالدہ حسین اور اسد محمد خان جیسے مصنفین کے منتخب افسانوں کا تجزیہ کیا گیا ہے تاکہ نسوانی نقطہ نظر کی ترقی اور اس کے سماجی و ثقافتی اثرات کو سمجھا جا سکے۔